DINAMIKA KINERJA PEGAWAI HOTEL: Peran Lingkungan Kerja, Kepemimpinan, Kompensasi, dan Motivasi - Siti Khayatun; Wanuri Wanuri; Yovita Mumpuni Hartarini (Sekolah Tinggi Ilmu Ekonomi Semarang, 2026)
Every organization (company) desires to improve work performance to achieve its goals. One crucial element that must be considered to achieve these goals is human resources (HR). This is because high-performing HR are able to drive the company's operations, thus impacting the achievement of company targets. However, HR performance can fluctuate due to various influencing factors, such as the work environment, leadership, compensation, and motivation. This study aims to: 1) analyze and explain the influence of the work environment on employee performance at the Patra Jasa Hotel Semarang; 2) analyze and explain the influence of leadership on employee performance at the Patra Jasa Hotel Semarang; 3) analyze and explain the influence of compensation on employee performance at the Patra Jasa Hotel Semarang; 4) analyze and explain the influence of motivation on employee performance at the Patra Jasa Hotel Semarang; and 5) analyze and explain the influence of the work environment, leadership, compensation, and motivation on employee performance at the Patra Jasa Hotel Semarang. This research method is descriptive quantitative. Data were collected through questionnaires, and the data analysis tool was multiple linear regression with quantitative descriptive analysis. The results of the study indicate: 1) There is a positive influence of work environment variables on employee performance, because the P-value of the work environment variable is 0.001 (P<0.05) so the proposed hypothesis is accepted. 2) There is no influence of leadership variables on employee performance, because the P-value of the leadership variable is 0.451 (P>0.05) so the proposed hypothesis is rejected. 3) There is a positive influence of compensation variables on employee performance, because the P-value of the compensation variable is 0.006 (P<0.05) so the proposed hypothesis is accepted. 4) There is no influence of motivation variables on employee performance, because the P-value of the motivation variable is 0.733 (P>0.05) so the proposed hypothesis is rejected. Suggestions in this study include: Leaders should improve employee space in the workplace, leaders should be able to generate creative ideas and create a conducive work environment, leaders should strive to provide a leadership model that employees can emulate, leaders should strive to provide appropriate incentives, and leaders should always provide support to employees.